Synthesis of High-Quality Biodiesel Using Feedstock and Catalyst Derived from Fish Wastes - Madhu D.; Arora R.; Sahani S.; Singh V.; Sharma Y.C. (My University, 2025)
A low-cost and high-purity calcium oxide (CaO) was prepared from waste crab shells, which were extracted from the dead crabs, was used as an efficient solid base catalyst in the synthesis of biodiesel. Raw fish oil was extracted from waste parts of fish through mechanical expeller followed by solvent extraction. Physical as well as chemical properties of raw fish oil were studied, and its free fatty acid composition was analyzed with GC-MS. Stable and high-purity CaO was obtained when the material was calcined at 800 °C for 4 h. Prepared catalyst was characterized by XRD, FT-IR, and TGA/DTA. The surface structure of the catalyst was analyzed with SEM, and elemental composition was determined by EDX spectra. Esterification followed by transesterification reactions were conducted for the synthesis of biodiesel. The effect of cosolvent on biodiesel yield was studied in each experiment using different solvents such as toluene, diethyl ether, hexane, tetrahydrofuran, and acetone. High-quality and pure biodiesel was synthesized and characterized by 1H NMR and FT-IR. Biodiesel yield was affected by parameters such as reaction temperature, reaction time, molar ratio (methanol:oil), and catalyst loading. Properties of synthesized biodiesel such as density, kinematic viscosity, and cloud point were determined according to ASTM standards. Reusability of prepared CaO catalyst was checked, and the catalyst was found to be stable up to five runs without significant loss of catalytic activity. © 2017 American Chemical Society.